Pacemakers are associated with a higher risk of late death and transplantation in the Fontan population. (1st May 2019) - Poh, Chin L.; Celermajer, David S.; Grigg, Leeanne E.; Kalman, Jonathan M.; McGuire, Mark A.; Gentles, Thomas L.; Radford, Dorothy J.; Bullock, Andrew; Disney, Patrick J.S.; Winlaw, David; du Plessis, Karin; d'Udekem, Yves
Abstract: Background: The need for permanent pacing has been identified as a predictor of poor outcomes in the late survivors of Fontan surgery. However, it is not clear if the need for a pacemaker is a surrogate marker of a declining Fontan state, or if pacing is deleterious to the Fontan circulation. Objectives: We sought to compare the long-term outcomes of propensity-matched Fontan patients with and without a permanent pacemaker. Methods: Patients who have survived Fontan completion with a documented history of cardiac arrhythmia were identified from the Australia and New Zealand Fontan Registry. Pacemaker insertion details, cardiac function and electrophysiological data were obtained for the patients with a permanent pacemaker. Survival analysis was performed with propensity score matching to compare late survival and outcomes in patients with versus without a pacemaker. Results: There was a total of 310 patients with a history of cardiac arrhythmia, of which 126 (41%) had a permanent pacemaker. After propensity-score matching, 99 pairs were generated (n = 198). Patients with a permanent pacemaker had a higher risk of death (HR 3.32 95% CI 1.60–6.90, p = 0.001) and death or transplantation (HR 3.55 95% CI 1.87–6.73, p < 0.001). Patients who were only paced atrially were not at a significantly increased risk of death or transplantation. However, patients who were ventricular paced >50% of the time were much more likely to encounter late death or transplantation (HR 3.82 95% CI 1.64–8.95, p = 0.002). Conclusions: Having a permanent pacemaker and needing ventricular pacing is likely associated with an increased risk of death and transplantation in patients with a Fontan circulation. Highlights: 8% of patients living with a Fontan circulation needed insertion of a permanent pacemaker. After propensity-score matching, patients with a permanent pacemaker had a higher risk of death and transplantation compared to those without. Patients who had ventricular pacing more than 50% of the time were at highest risk of death and transplantation, and systemic ventricular dysfunction.